2022
DOI: 10.1039/d2fo01808j
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofin vitrobioaccessibility of carotenoids and phenolic compounds in a model milk–mandarine beverage

Abstract: Mandarine juice is one of the richest sources of β-cryptoxanthin and flavonoids, which have been positively associated with bone mineral density. Carotenoids are lipophilic isoprenoid compounds with a complex absorption...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
3
1
Order By: Relevance
“…In contrast to our study,Oliveira and Pintado (2015) reported that the bioaccessibility indices of peach-and strawberry-enriched yogurt were 20% and 53%, respectively Stinco et al (2022). revealed that the content of milk fat in milk-mandarine beverages increased TA B L E 6 Bioaccessibility indexes of the samples.…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our study,Oliveira and Pintado (2015) reported that the bioaccessibility indices of peach-and strawberry-enriched yogurt were 20% and 53%, respectively Stinco et al (2022). revealed that the content of milk fat in milk-mandarine beverages increased TA B L E 6 Bioaccessibility indexes of the samples.…”
contrasting
confidence: 99%
“…( 2021 ) who reported a decrease in the TPC values of yogurt incorporated into olive pomace during the intestinal process. The higher TAC values of control kefir during the gastric process conditions might be explained by the following approaches affecting the antioxidant mechanisms: (i) lactoferrin, serum albumin, casein, uric acid, beta‐carotene, and retinol composition of kefir (Cervato et al., 1999 ; Perna et al., 2014 ; Stinco et al., 2022 ); (ii) amino acids (phenylalanine, methionine, cysteine, tryptophan, etc.) and bioactive peptides derived from kefir protein (Aloglu & Oner, 2011 ; Gamba et al., 2020 ; Power et al., 2013 ); (iii) the scavenging/reducing of reactive oxygen species and iron of starter microbiota (Biadała & Adzahan, 2021 ; Liu et al., 2005 ; Parrella et al., 2012 ; Yilmaz‐Ersan et al., 2018 ); and (iv) lipophilic components such as conjugated linoleic acid and liposoluble vitamins (vitamin E) released in acidic conditions (Badr El‐Din & Omaye, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations